Az egyetemi szabadalmaztatás intézményi és regionális befolyásoló tényezői Európában - Varga, Attila; Horváth, Márton (Közép-Európai Közlemények, 2013)
Over the past 30 years universities have been increasingly considered as key instruments of regional economic development policy in many countries of the World. Contrary to the US where studying the entire universe of academic institutions is a real possibility, thanks to the availability of regularly collected nation-wide information on all universities, in Europe no such coordinated data collection efforts are in existence. This is why the EUMIDA database constitutes such a pioneering work. In this paper we take advantage of the availability of the EUMIDA data for scientific investigations. We selected to focus on one specific, widely promoted form of academic entrepreneurship: university patenting. Following what the literature teaches us about the likely institutionaland regional level impacts on academic entrepreneurship we utilize EUMIDA information to build as large a sample as possible to study European-wide tendencies of university patenting. Regional level impacts are investigated at the NUTS 3 level, which is in itself a novelty in the literature. This lower level of data aggregation opens the possibility to get closer to the spatial level of metropolitan areas where university-industry interactions most probably take place.